Targeted metabolomic profiling of RAW 264.7 cells infected with Brucella canis identifies time-dependent metabolic changes - Woo Bin Park; Su Min Kyung; Suji Kim; Young Ju Lee; Han Sang Yoo (PLoS ONE, 2026)
Canine brucellosis caused by Brucella canis is gaining public-health relevance as companion-dog ownership and close human–animal contact increase. Yet mechanistic insight into B. canis host responses remains limited at the pathway level. To address this gap, we profiled infection-associated metabolic responses in RAW 264.7 cells across multiple post-infection time points using targeted metabolomics (CE–MS). We observed a coherent, time-ordered pattern with the largest shifts at 24 h: arginine, hydroxyproline, choline, cysteine, β-alanine, and glycerol-3-phosphate showed pronounced decreases, and tyrosine decreased modestly; α-ketoglutarate displayed a lower mean at 12 h. Unsupervised analyses separated infected and control groups over time (PCA PC1 = 59.4%, PC2 = 16.7%; 76.1% cumulative), providing an orthogonal summary of the temporal divergence. A supplementary sensitivity analysis (Minimum Cell Loss) was included as exploratory contextual information regarding potential cell-number effects, although direct measurements of infection efficiency and macrophage viability were not performed. An integrated pathway schematic summarizes metabolite associations related to nitric-oxide–related, mitochondrial/energy, redox/glutathione, extracellular-matrix, membrane-lipid, and neuroimmune-related pathways. Together, these results deliver a time-resolved view of B. canis –macrophage metabolic responses and delineate prioritized avenues for targeted mechanistic validation.